STRATEGIES FOR ENHANCING THE COMPETITIVENESS OF PRIVATE HIGHER EDUCATION INSTITUTIONS THROUGH INDUSTRY PARTNERSHIP PROGRAMS: AN ANALYSIS IN THE ERA OF DIGITALIZATION AND AI (2019–2024) - Ajeng Handayani Purwaningrum; Denny Ammari Ramadhan (Published by the Faculty of Economics and Business, University of Labuhanbatu, North Sumat, 2026)
PURPOSE – This study analyzes the evolution of strategies for enhancing the competitiveness of private higher education institutions through industry partnerships during the 2019-2024 period. It integrates an analysis of the impact of the COVID-19 pandemic, the acceleration of digital transformation, and the emergence of artificial intelligence capabilities.METHODOLOGY - Using a sequential mixed-method design, the study draws on quantitative data from 312 respondents across 15 private higher education institutions in the Riau Islands and qualitative data from 32 interviews with institutional leaders and six focus group discussions with industry partners. The findings identify developments in partnership models, digital maturity trajectories, and emerging challenges arising from competition with EdTech platforms.FINDING – The results show that: (1) the pandemic accelerated the adoption of digital transformation, with digital-enabled partnerships increasing from 34% in 2019 to 78% in 2024; (2) AI-integrated capabilities have become a new competitive differentiator, as institutions implementing AI-powered learning analytics achieved a 23% improvement in graduate employment outcomes; and (3) institutional partnership capacity increased significantly through the implementation of the Merdeka Belajar Kampus Merdeka (MBKM) policy in 2020, although sustainability remains challenged by limited financial resources and gaps in faculty digital literacy